Black Hammer. Volume 5, Reborn. Part I - Lemire, Jeff (Lemire, Jeff. Black hammer, 2022)
"In 1986, Black Hammer and the rest of Spiral City's greatest superheroes seemingly died defeating the cosmic despot known as Anti-God and saving the world. But one woman refused to believe they were truly gone: Lucy Weber, the daughter of Black Hammer. Learning that her dad had sacrificed himself to save the other heroes, Lucy soon took up the mantle of Black Hammer and carried on the legacy of her father as the world's greatest superhero"--